PENINGKATAN KEMAMPUAN MENJAWAB PERTANYAAN DAN PRESTASI BELAJAR IPA MELALUI MOBEL PBL (PROBLEM BASED LEARNING) BERBANTUAN MEDIA TUAL BAN PADA SISWA KELAS VII B SEMESTER 1 MTSN 4 KEBUMEN KABUPATEN KEBUMEN TAHUN PELAJARAN 2019/2020 - Mutmainnah (CV. Amerta Media, 2020)
Based on the results of research achieved in this Classroom Action Research it can be implied that PBL (Problem Based Learning) with Question and Answer Card (Tual Ban) can be used to improve the competency in answering questions and students' learning achievement, especially for students of Class VIIB Semester 1 MTsN Kebumen. ability to answer questions Seen from the pre cycle with an average value of 6.75 increased by 1.16 to 7.91 in cycle 1, and increased by 0.92 to 8.83 in cycle 2. And an increase in student achievement, from pre cycle with an average value of 5.25 increased by 1.91 to 7.16 in cycle 1 and increased by 0.55 to 7.71 in cycle 2Key Words: learning achievement, Problem Based Learning, Tual Ban Media